2014
DOI: 10.1177/1040638714545506
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a fluorescent antibody test for the detection of antibodies against epizootic bovine abortion

Abstract: The current study was directed at developing and validating an indirect fluorescent antibody test (IFAT) capable of detecting antibodies specific for the agent of epizootic bovine abortion (aoEBA). Sensitivity and specificity was determined by comparing antibody titers from 114 fetuses infected with aoEBA with 68 fetuses diagnosed with alternate infectious etiologies. Data established specificity at 100% and sensitivity at 94.7% when cutoff criteria for a positive test were assigned at a titer of ≥1,000. Poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The P. abortibovis-specific IFAT assay described in these studies was reported to be >98% sensitive and >95% specific when diagnostically applied to bovine fetal fluids [29]; a small percentage of fetal fluid samples were believed to contain low-titer cross-reactive antibodies. Sensitivity and specificity of the IFAT assay have yet to be defined for mature animals.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The P. abortibovis-specific IFAT assay described in these studies was reported to be >98% sensitive and >95% specific when diagnostically applied to bovine fetal fluids [29]; a small percentage of fetal fluid samples were believed to contain low-titer cross-reactive antibodies. Sensitivity and specificity of the IFAT assay have yet to be defined for mature animals.…”
Section: Discussionmentioning
confidence: 83%
“…Samples were also collected from heifers in Trial #4 at 0 DPV (n = 58) and on day of challenge at either 146 or 181 DPV (n = 34). An indirect fluorescent antibody test (IFAT) was conducted as previously described [29]. Briefly, single-cell suspensions of P. abortibovis-infected SCID mice splenocytes, adjusted to a final concentration of 3.3 × 10 7 cells/mL with PBS, were dispersed evenly over each well surface of 12-well Teflon-coated slides, fixed in acetone, air-dried and stored at −20 • C. Fluid samples were serially diluted with PBS, added to antigen-coated wells and incubated at room temperature for 20 min.…”
Section: Serologic Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Sera b, c, and d are referred to as immune sera and e, f, and g as EBA-negative controls. The presence of P. abortibovis antibody was confirmed in serum from P. abortibovis -exposed animals and absence in those with no known exposure by indirect fluorescent antibody test (IFAT) as previously described ( Blanchard et al 2014 ). Antibody binding was detected with alkaline phosphatase-conjugated anti-mouse IgG (H&L) (Vector Laboratories, Burlingame, CA) or anti-bovine IgG (H&L) (Jackson ImmunoResearch Laboratories, Inc., West Grove, PA) as appropriate, followed by NBT/BCIP substrate (Roche Diagnostics, Indianapolis, IN).…”
Section: Methodsmentioning
confidence: 99%
“…Identification of this Deltaproteobacterium, Pajaroellobacter abortibovis , allowed for the development of new diagnostic methodologies ( Blanchard et al 2010 , 2014 ; Brooks et al 2011 ). The visualization of P. abortibovis through immunohistochemistry and DNA-based diagnostic techniques using PCR have increased diagnostic sensitivity ( Anderson et al 2006 ; Brooks et al 2016 ).…”
mentioning
confidence: 99%